2002
DOI: 10.1073/pnas.212449899
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the single-strand annealing domain of human RAD52 protein

Abstract: In eukaryotic cells, RAD52 protein plays a central role in genetic recombination and DNA repair by (i) promoting the annealing of complementary single-stranded DNA and (ii) stimulation of the RAD51 recombinase. The single-strand annealing domain resides in the N-terminal region of the protein and is highly conserved, whereas the nonconserved RAD51-interaction domain is located in the C-terminal region. An N-terminal fragment of human RAD52 (residues 1-209) has been purified to homogeneity and, similar to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
291
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(311 citation statements)
references
References 27 publications
17
291
1
Order By: Relevance
“…Moreover, an unusual nonglobular tower domain interrupts one of the BRCA2 OB folds (16) and may act to promote BRCA2 binding to dsDNA-ssDNA junctions (39). Consistent with a bypass mechanism, we found that the structurally distinct ssDNA-binding domain from Rad52 (40,41) can function in HDR correction in the Brca2 mutant cells. Besides the DNA-binding domain, other parts of the BRCA2 protein may provide more complex levels of control of BRCA2 function, including the recently identified cell cycle-regulated phosphorylation site that modulates Rad51 binding to the C terminus of BRCA2 (17).…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, an unusual nonglobular tower domain interrupts one of the BRCA2 OB folds (16) and may act to promote BRCA2 binding to dsDNA-ssDNA junctions (39). Consistent with a bypass mechanism, we found that the structurally distinct ssDNA-binding domain from Rad52 (40,41) can function in HDR correction in the Brca2 mutant cells. Besides the DNA-binding domain, other parts of the BRCA2 protein may provide more complex levels of control of BRCA2 function, including the recently identified cell cycle-regulated phosphorylation site that modulates Rad51 binding to the C terminus of BRCA2 (17).…”
Section: Discussionsupporting
confidence: 66%
“…The described sequence similarity allowed us to model the structure of plant RAD52 homologs on the determined structures of the N-terminal domain of human RAD52 (Kagawa et al, 2002;Singleton et al, 2002). As expected by the relatively long corresponding regions and few insertion/deletion points ( Figure 1; see Supplemental Figure 1 online), the same topology and structure features of human RAD52 are present in the models of A. thaliana RAD52 homologs (see Supplemental Figure 2 online).…”
Section: Higher Plants Include a Family Of Rad52 Homologs Encoding Sementioning
confidence: 80%
“…As expected by the relatively long corresponding regions and few insertion/deletion points ( Figure 1; see Supplemental Figure 1 online), the same topology and structure features of human RAD52 are present in the models of A. thaliana RAD52 homologs (see Supplemental Figure 2 online). The residues corresponding to the two known RAD52 DNA binding sites (Kagawa et al, 2002;Singleton et al, 2002) are mostly conserved in the plant RAD52 homologs (Figure 1) and form similar sites, including both the positively charged groove and the second DNA binding site (see Supplemental Figures 2B and 2C online). The alpha helix of the RAD52 stem region (residues 145 to 163 in At1g71310, corresponding to residues 159 to 134 in human RAD52) demonstrated a repetitive pattern of sequence conservation.…”
Section: Higher Plants Include a Family Of Rad52 Homologs Encoding Sementioning
confidence: 99%
See 1 more Smart Citation
“…Rad52 repair foci colocalize with DSBs in vivo in yeast with one foci recruiting multiple DSBs (Lisby et al, 2003). Furthermore, the structure of the single-strand annealing domain of human Rad52 was shown to form an 11-subunit ring (Kagawa et al, 2002;Singleton et al, 2002). The Rad54 protein cooperates with Rad51 in the homologous DNA pairing reaction and is involved in the dissociation of Rad51 from nucleoprotein complexes formed on dsDNA (Sigurdsson et al, 2002;Solinger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%